Bicondylar Hoffa Fracture Successfully Treated with Headless Compression Screws - Lee, Sang Yang (Hindawi Publishing Corporation, 2014)
Bicondylar coronal plane fracture, eponymically named Hoffa fractures, is an extremely rare injury. We present a case of isolated unilateral bicondylar Hoffa fracture that was successfully treated with open reduction and internal fixation using headless compression screws with satisfactory results. We inserted posteroanteriorly oriented Acutrak screws perpendicular to the fracture plane via lateral parapatellar arthrotomy, which provided excellent compression across the fracture.